2017
DOI: 10.2147/idr.s130203
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic distribution of multidrug-resistant and extensively drug-resistant tuberculosis in northern Thailand

Abstract: BackgroundMultidrug/extensively drug-resistant tuberculosis (M/XDR-TB) is a major public health problem, and early detection is important for preventing its spread. This study aimed to demonstrate the distribution of genetic site mutation associated with drug resistance in M/XDR-TB in the northern Thai population.MethodsThirty-four clinical MTB isolates from M/XDR-TB patients in the upper northern region of Thailand, who had been identified for drug susceptibility using the indirect agar proportion method from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 33 publications
5
13
0
1
Order By: Relevance
“…27 However, a retrospective investigation during 2008-2011 found only 35.3% of 34 MDR and XDR-TB isolates from northern Thailand carrying the katG mutation at codon 315, together with others 10 loci. 4 Four mutation patterns within the fabG1-inhA promoter were confirmed in this study. The rate of 20.6% for the most common genotypes, −15 (C>T), was comparable to the global frequencies: −15 (C>T) accounted for 19.2% of inhA promoter mutation.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…27 However, a retrospective investigation during 2008-2011 found only 35.3% of 34 MDR and XDR-TB isolates from northern Thailand carrying the katG mutation at codon 315, together with others 10 loci. 4 Four mutation patterns within the fabG1-inhA promoter were confirmed in this study. The rate of 20.6% for the most common genotypes, −15 (C>T), was comparable to the global frequencies: −15 (C>T) accounted for 19.2% of inhA promoter mutation.…”
Section: Discussionsupporting
confidence: 73%
“…24 However, the study of 34 MDR and XDR-TB isolates in 2005-2012 in northern Thailand reported eight rpoB mutations with no predominant codon including 588 (26.5%), 589 (26.5%), 526 (23.5%), 571 (20.6%), 531 (17.7%), 545 (17.7%), 564 (11.8%), and 574 (11.8%). 4 Here, the S522L rarely found in rpoB mutant strains was discovered in an MDR-TB isolate. The S522L was found to involve in RIF resistance and rifabutin susceptibility.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A previous report found a high prevalence of the katG S315T gene mutation among HR-TB/MDR-TB/XDR-TB strains (58.7%-68.6%) in Thailand. 16,17 The prevalence of katG S315T varied according to the geographic region: Southeast Asia (78.4%), 18 Vietnam (85.3%), 19 Myanmar (61.2%), 20 Taiwan (29.3%), 6 Japan (25%), 10 India (67.6%), 21 Sri Lanka (67.8%), 22 Romania (52.8%), 23 Cameroon (64%), 24 and the United States (38%). 8 The different ranges of MIC found for each mutation gene can be explained by gene variation.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have shown specificities of gene mutations in predicting kanamycin [9] [10] [11] and ofloxacin resistance [11] [12] [13] [14]. Many studies have been conducted on genotypic and phenotypic characteristics of drug resistant M. tuberculosis; however, this kind of study is rare in Thailand [15]. Better understanding of the molecular mechanisms of drug resistance in pre-XDR-TB and XDR-TB strains can contribute to the improvement of existing techniques in detecting drug resistance and help to explore new target sites and develop new diagnostic tools.…”
Section: Xdr-tb Normally Develops From Multi-drug Resistant Tuberculomentioning
confidence: 99%